Perilaku Masyarakat Terkait Sanitasi Lingkungan pada Wilayah Lahan Basah di Tepian Sungai Siak - Nafa Azzarah; Febriana Sabrian; Ari Rahmat Aziz (Jurnal Kesehatan Komunitas, 2026)
Environmental sanitation is an effort to optimize environmental conditions to prevent the spread of disease and improve public health. Inadequate implementation of environmental sanitation, including access to clean water and use of unsanitary toilets, contributes to an increase in environmentally based infectious diseases. This research aims to explore community behavior related to environmental sanitation in the wetland area along the Siak River. This study used a descriptive qualitative approach through semi-structured interviews with six informants, selected by purposive sampling, and analyzed using thematic analysis. Some practices reported by the informants align with environmental health standards, such as disposing of waste at designated landfills, managing drinking water, and maintaining household environments. However, there are still practices that do not align with health standards, such as disposing of feces into rivers and using river water for household needs. Poor sanitation practices, if carried out over a long period of time, will endanger health, quality of life, and the environment. These practices are attributed to poor community habits and economic constraints that hinder informants from constructing adequate sanitation facilities. The role of relevant institutions is needed in empowering and improving sanitation infrastructure so that environmental sanitation practices that meet health standards can be implemented.